The large-scale implementation of adaptation and mitigation actions in the agriculture and food sector. Draft for discussion. - Cooper, Peter J.M.; Cappiello S; Vermeulen, Sonja J.; Campbell, Bruce M. (2012)
NOTE: This paper was a draft for discussion and is now published in its final form at https://ccafs.cgiar.org/publications/large-scale-implementation-adaptation-and-mitigation-actions-agriculture. The discussion draft is no longer available.